Impact of low skeletal muscle mass and quality on clinical outcomes in patients with head and neck cancer undergoing (chemo)radiation - Bardoscia, Lilia; Besutti, Giulia; Pellegrini, Massimo; Pagano, Maria; Bonelli, Candida; Bonelli, Efrem; Braglia, Luca; Cozzi, Salvatore; Roncali, Massimo; Iotti, Cinzia; Pinto, Carmine; Pattacini, Pierpaolo; et al. (Frontiers in Nutrition, 2022)
The study aimed to explore the impact of low skeletal muscle mass and quality on survival outcomes and treatment tolerance in patients undergoing radical chemo-radiation therapy for head and neck cancer (HNC). This is significant given the growing interest in sarcopenia as a possible negative predictive/prognostic factor of disease progression and survival. From 2010 to 2017, 225 patients were included in the study. Pre-treatment computed tomography (CT) scans of HNC patients undergoing (chemo)radiation therapy were retrospectively reviewed. The skeletal muscle area, normalized for height to obtain the skeletal muscle index (SMI), the skeletal muscle density (SMD) and the intramuscular adipose tissue area (IMAT) were measured at the level of the L3 vertebra. Low SMD and low SMI were defined according to previously reported thresholds, while high IMAT was defined using population-specific cut-point analysis. SMI, SMD, and IMAT were also measured at the proximal thigh (PT) level and tested as continuous variables. Clinical morpho-functional parameters, baseline nutritional markers with a known or suspected impact on HNC treatment, clinical outcomes and sarcopenia were also collected. In multivariate analyses, adjusted by age, sex, stage, diabetes, body mass index (BMI), and weight loss, L3-SMI was not significantly associated with survival, while poor muscle quality was negatively associated with overall survival (OS) (HR = 1.88, 95% CI = 1.09–3.23, p = 0.022 and HR = 2.04, 95% CI = 1.27–3.27, p = 0.003, for low L3-SMD and high L3-IMAT, respectively), progression-free survival (PFS) (HR = 2.26, 95% CI = 1.39–3.66, p = 0.001 and HR = 1.97, 95% CI = 1.30–2.97, p = 0.001, for low L3-SMD and high L3-IMAT, respectively) and cancer-specific survival (CSS) (HR = 2.40, 95% CI = 1.28–4.51, p = 0.006 and HR = 1.81, 95% CI = 1.04–3.13, p = 0.034, for low L3-SMD and high L3-IMAT, respectively). Indices at the PT level, tested as continuous variables, showed that increasing PT-SMI and PT-SMD were significant protective factors for all survival outcomes (for OS: HR for one cm2/m2 increase in PT-SMI 0.96; 95% CI = 0.94–0.98; p = 0.001 and HR for one HU increase in PT-SMD 0.90; 95% CI = 0.85–0.94; p < 0.001, respectively). PT-IMAT was a significant risk factor only in the case of CSS (HR for one cm2 increase 1.02; 95% CI = 1.00–1.03; p = 0.046). In conclusion, pre-treatment low muscle quality is a strong prognostic indicator of death risk in patients affected by HNC and undergoing (chemo)radiotherapy with curative intent.